Chinese patent law a practical guide - Li, Yongbo; Kong, Fanwen; Yang, Yang, (Antitrust lawyer) (Kluwer Law International B.V., 2021)
Numerous non-Chinese entities seek patents in China, and allegations of infringement are not uncommon. Patent rights are different from general civil rights. They are based on administrative authorization, and the scope of protection is subject to the content of the claims recorded in the patent documents. In this invaluable guide to Chinese patent law and the rules applicable to infringement challenges, the authors-all members of a leading Chinese law firm with vast experience in advising foreign clients-bring their expertise in real-world patent litigation, reinforced with an abundance of relevant court decisions to introduce the Chinese patent regime in a systematic and practical manner.